Wajib Daftar Perusahaan dan Akibat Hukumnya Di Indonesia - Herman Susetyo, Budiharto, Rindito Hermawan, (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
One of the efforts to create and provide legal protection as well as providing guidance, direction, supervision and creating a healthy business climate, the government issued Law - Act No. 3 of 1982 on Corporate Registry. The problem in this research is: How does the implementation of company registration in Indonesia and sanctions if the company does not carry a list of companies. How government policy to encourage the implementation of company registration. This study aims to determine the various technical aspects of the company and some of the sanctions list will be made if the company does not carry out the provisions of company registration and determine government policies encourage companies list.